Soft Skills as a Tool for Improving Building Artisans’ Employability to Achieve Sustainable Development Goal (SDG) 8 - Mohamad Shaharudin Samsurijan; Andrew Ebekozien; Mohamed Ahmed Hafez; Nooramira Ghazali; Wellington Didibhuku Thwala; Romeo Osayande Aigbe (Journal of Construction in Developing Countries, 2026)
In the construction industry, the role of building artisans is crucial. However, skills development can pose challenges to artisans’ employability in countries with weak apprenticeship schemes. Studies have shown that soft skills can enhance employability, and by extension, improve decent work and economic growth (Sustainable Development Goal 8 [SDG 8]). Nevertheless, studies examining the role of soft skills in improving the employability of Nigerian building artisans in relation to SDG 8 remain scarce. This study assesses the role of soft skills in enhancing artisans’ employability and proposes measures to improve skills development, thereby contributing to the achievement of SDG 8. Using a qualitative research design, the researchers engaged 36 participants in Lagos and Abuja, Nigeria, and achieved data saturation. The data were manually analysed under two themes, and the results are presented accordingly. The findings reveal that soft skills development can enhance the employability of building artisans and contribute to the achievement of SDG 8. The findings also categorise measures to improve soft skills development for building artisans’ employability, and by extension, the achievement of SDG 8, directed at relevant government agencies, employers and employees. This research contributes to promoting the implementation of soft skills to enhance the employability of Nigerian building artisans and to, consequently, support the achievement of SDG 8.